2020
DOI: 10.1001/jamadermatol.2019.5014
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on the Use of Artificial Intelligence for Skin Cancer Screening

Abstract: IMPORTANCEThe use of artificial intelligence (AI) is expanding throughout the field of medicine. In dermatology, researchers are evaluating the potential for direct-to-patient and clinician decision-support AI tools to classify skin lesions. Although AI is poised to change how patients engage in health care, patient perspectives remain poorly understood.OBJECTIVE To explore how patients conceptualize AI and perceive the use of AI for skin cancer screening. DESIGN, SETTING, AND PARTICIPANTSA qualitative study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
205
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(239 citation statements)
references
References 20 publications
9
205
0
5
Order By: Relevance
“…Consistent with previous studies of public perspectives about health AI [16,[23][24][25], participants' support for health AI scenarios was linked to their perceived public benefit of the scenarios, with people being most supportive when they believed that AI could bring an important new capability to a problem beyond what humans could contribute. Each of three health AI research scenarios were viewed as being acceptable by most of the participants of the focus groups (Table 3).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Consistent with previous studies of public perspectives about health AI [16,[23][24][25], participants' support for health AI scenarios was linked to their perceived public benefit of the scenarios, with people being most supportive when they believed that AI could bring an important new capability to a problem beyond what humans could contribute. Each of three health AI research scenarios were viewed as being acceptable by most of the participants of the focus groups (Table 3).…”
Section: Discussionsupporting
confidence: 75%
“…Most published studies have focused on the views of patients who may not be representative because they stand to benefit from AI applications [16]. Further, most published studies have focused on computer vision health AI applications in radiology and dermatology, which represent only a small fraction of the potential applications of AI in health [23][24][25]. Additionally, there is a need to understand public perspectives versus patient perspectives, because health AI research may rely on large datasets that include information about people who do not have health conditions and/or do not stand to benefit directly from the research.…”
Section: Introductionmentioning
confidence: 99%
“…16 Further, most published studies have focused on computer vision health AI applications in radiology and dermatology, which represent only a small fraction of the potential applications of AI in health. [23][24][25] Additionally, there is a need to understand public perspectives versus patient perspectives, because health AI research may rely on large datasets that include information about people who do not have health conditions and/or do not stand to benefit directly from the research. Accordingly, the objective of this study was to learn more about how members of the general public perceive health data being used for AI research.…”
Section: Open Accessmentioning
confidence: 99%
“…"(26) A recent small study has shown that dermatology patients are receptive to AI based diagnostic methods for detection of skin cancer within the context of a human physician-patient relationship. (27) This suggests that the reluctance to adopt AI based diagnostic aids is not related to negative patient attitudes. Lindsell et al go on to state that "Designing a useful AI tool in health care should begin with asking what system change the AI tool is expected to precipitate.…”
Section: Discussionmentioning
confidence: 99%